2021
DOI: 10.1111/pace.14382
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and proposed mechanisms of QRS morphology observed during the left bundle branch pacing procedure

Abstract: Background:In performing left bundle branch pacing (LBBP), various QRS morphologies are observed as the lead penetrates the ventricular septum (VS). This study aimed to evaluate these characteristics and infer the mechanism underlying each QRS morphology. Methods:In 19 patients who met the strict criteria for LBB capture, we classified the QRS morphologies observed during the LBBP procedure into seven patterns, the first five of which were determined by the depth of penetration: right ventricular septal pacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…LVSP, on the other hand, captures left ventricular septal myocardium, resulting in direct left-to-right septal activation, preserving interventricular dyssynchrony. The terminal R′/r′ wave duration in lead V1, which indicates delayed right ventricular excitation, was significantly longer in LBBP than in LVSP ( 17 ), also indicating that LBBP caused more pronounced interventricular dyssynchrony than LVSP. However, this interventricular synchrony of LVSP may not be physiological.…”
Section: Comparison Of Lbbp and Lvsp In Interventricular Synchronymentioning
confidence: 99%
See 1 more Smart Citation
“…LVSP, on the other hand, captures left ventricular septal myocardium, resulting in direct left-to-right septal activation, preserving interventricular dyssynchrony. The terminal R′/r′ wave duration in lead V1, which indicates delayed right ventricular excitation, was significantly longer in LBBP than in LVSP ( 17 ), also indicating that LBBP caused more pronounced interventricular dyssynchrony than LVSP. However, this interventricular synchrony of LVSP may not be physiological.…”
Section: Comparison Of Lbbp and Lvsp In Interventricular Synchronymentioning
confidence: 99%
“…It is essentially LBBP with bipolar pacing configuration ( Figure 1C ), with the cathode tip capturing LBB and the anode ring capturing RBB area. Shimeno et al also revealed that the terminal R′/r′ wave duration of LBBP with bipolar pacing configuration is shorter than that of LVSP, presumably due to the contribution of the anodal capture during bipolar pacing ( 17 ). In addition, some previous studies and case reports have shown that LBBP can shorten the QRS duration of intrinsic RBBB or even completely correct RBBB ( 19 23 ), while LVSP cannot, but the underlying mechanism remains unclear and needs further study.…”
Section: Comparison Of Lbbp and Lvsp In Interventricular Synchronymentioning
confidence: 99%
“…Shimeno et al ( 18 ) observed that the mean threshold of anodal capture in NSLBBP was 4.9 ± 1.2V @ 0.4ms, and that the paced QRS duration was significantly shorter than that without anodal capture (121 ± 9 ms vs. 135 ± 8 ms). Similarly, the average threshold for simultaneous capture of LBB and RBB in cathode tip and anode ring bipolar pacing mode in Lin et al ’s study was 2.7 V @ 0.5 ms ( 26 ).…”
Section: Unipolar Tip Pacing and Bipolar Tip Pacing Configurationmentioning
confidence: 99%
“…When the lead is advancing from the right ventricular septum to the left, the morphology of paced QRS complex changes dynamically, as seen by the W-shaped notch at the nadir of the QRS complex in lead V1 gradually moving to the end of that and eventually presenting a pseudo-RBBB pattern (13,14). This is because LBBP can directly capture the LBB, causing the excitation of the left ventricular lateral wall to be to accelerated while the excitation of the right ventricle (RV) to be delayed (17)(18)(19)(20). LBBP can be divided into two types: selective LBBP (SLBBP), which involves only LBB capture, and nonselective LBBP (NSLBBP), which involves LBB and surrounding myocardium capture.…”
Section: Left Bundle Branch Pacing Technique and Ecg Featuresmentioning
confidence: 99%
“…21,22 LBBP was defined as LBB capture, which was confirmed when all of the following criteria were satisfied: can be classified into seven patterns based on the lead depth or pacing output. 23 Deep septal pacing (DSP) is the pacing modality in which there is a Qr pattern just after the appearance of the late-R wave in the V1 lead for the first time during lead penetration; Shimeno et al…”
Section: Definition Of Left Bundle Branch Pacing (Lbbp)mentioning
confidence: 99%